Dielectric analysis of the interaction of nematic liquid crystals with carbon nanotubes. Issue 3 (19th February 2018) - Peterson, Matthew S. E.; Georgiev, Georgi; Atherton, Timothy J.; Cebe, Peggy
ABSTRACT: Multi-walled carbon nanotubes (MWCNTs) have been shown to self-organise, and when added as a guest to form a nanocomposite, their director couples with an organic liquid crystal (LC) host. Here, effects of MWCNTs on the low-frequency dielectric properties and Fréedericksz transition of the LC 4-cyano-4ʹ-pentylbiphenyl (5CB) are studied. Anti-parallel electro-optic cells were filled with nanocomposites at weight percent concentrations of MWCNT to 5CB of: 0 (neat), 0.01, 0.10, 0.20, and 0.50. Low concentration was chosen to minimise Van der Waals attraction normally responsible for aggregation of MWCNTs. Dielectric relaxation spectroscopy was used to study interactions between MWCNTs and 5CB at frequencies from 20 Hz to 1 MHz. We propose a mechanism based upon measurements of the complex dielectric function which suggests that MWCNTs act as a slow-moving boundary within the sample cell at low frequencies and low applied electric fields, where the MWCNTs reorient along with the 5CB LC molecules. At higher frequencies and larger applied electric fields, the 5CB molecules rotate about their long axes while motion of the MWCNTs is frozen out. GRAPHICAL ABSTRACT: